Masdevallia coccinea - Karremans Lok, Adam Philip (2019)
Masdevallia coccinea is a widely distributed species in the Eastern Cordillera of Colombia, being locally abundant. It is “a most remarkable plant”, with large, bright red flowers. The lateral sepals are tail-less, and the tail of the dorsal sepal is commonly erect, sometimes directed either slightly backwards or forwards.